Evil, Hiddenness, and Nonbelief in Abū al-Barakāt al-Baghdādī's Commentary on Ecclesiastes: A Contemporary Philosophical Reflection - Abdalla, Bakinaz (TheoLogica, 2025)
The problem of evil has consistently challenged theistic belief. This challenge appears in both contemporary and medieval philosophical sources, including those written by Jewish and Muslim philosophers and theologians. Treatments of the problem vary across historical contexts. This study examines a significant, yet understudied, engagement with this problem by Abū al-Barakāt al-Baghdādī (a 12th-century Jewish philosopher who converted to Islam) in his commentary on Ecclesiastes, proposing to contribute to research on both intellectual history, within the realms of Islamic and Jewish philosophy and theology, and philosophy of religion. First, I reconstruct the problem of evil as presented in Abū al-Barakāt's Judeo-Arabic commentary on Ecclesiastes (extant in manuscript form), highlighting the surrounding philosophical and theological trends that shaped its overall perspective. Second, reflecting a deeper philosophical dimension of the reconstructed problem of evil, I analyze it through the lens of contemporary philosophy of religion, particularly the evidential argument from evil and relevant aspects of the problem of divine hiddenness. I argue that Abū al-Barakāt's formulation, distinct from customary articulations of the problem in his intellectual milieu, anticipates atheistic challenges posed by the evidential argument and divine hiddenness. Finally, I propose that potential complementary responses to these challenges can be developed by analyzing (1) Abū al-Barakāt's conception of taqlīd (conformism) in light of Alvin Plantinga's concept of the basicality of belief, and (2) his use of the Islamic doctrine of al-Qaḍāʾwa al-Qadar (divine Decree and Predestination), which allows for a skeptical response.